77. Out of Sight, Out of Mind: Impact of an Antimicrobial Stewardship Bundle on Fluoroquinolone Utilization. (31st December 2020) - Black, Blade W; Harding, Stephanie; Beadle, Kathy
Abstract: Background: Fluoroquinolones are broad spectrum antimicrobials associated with a growing list of adverse effects, such as Clostridioides difficile infection, arrhythmias, central nervous system effects, tendon rupture and aortic aneurysm. Due to increasing concerns regarding adverse events and growing resistance, the antimicrobial stewardship team at Wesley Healthcare implemented a bundle aimed at reducing fluoroquinolone usage beginning in June 2017. The components of this bundle included suppression of fluoroquinolone susceptibility in Enterobacteriaceae isolates, removal of fluoroquinolones as first line options on order sets, and introduction of a respiratory specific antibiogram. Methods: The objective was to evaluate the impact of the stewardship bundle on fluoroquinolone utilization. The primary outcome was ciprofloxacin and levofloxacin usage in days of therapy per 1000 inpatient days (DOT) collected at monthly intervals for 24 months before and after intervention. Overall antimicrobial usage in DOT served as a control variable. The secondary outcomes were E. coli and P. aeruginosa susceptibility to ciprofloxacin measured at the same time points as the primary outcome. An interrupted time-series analysis using segmented regression was performed for all variables. Results: The mean monthly levofloxacin usage was reduced from 14.1 (95% CI, 12.7 - 15.4) to 8.4 (95% CI, 7.6 - 9.3) DOT. The mean monthly ciprofloxacin usage was reduced from 26.9 (95% CI, 24.6 - 29.4) to 15.8 (95% CI, 14.0 - 17.5) DOT. The trend in levofloxacin usage was reduced (p=0.035), while a pre-existing downward trend in ciprofloxacin usage was unchanged (p=NS). Overall antimicrobial usage increased, likely due to increasing hematology/oncology populations during the study period. There were no differences in E. coli or P. aeruginosa susceptibilities observed. Conclusion: This antimicrobial stewardship bundle may be a useful intervention to reduce fluoroquinolone usage. The bundle may be of particular utility in reducing levofloxacin usage, as our results demonstrated a change in both its usage and trend in usage. Disclosures: All Authors : No reported disclosures